Factores que predisponen a la ingesta de organosoforados en pacientes atendidos en el Área de Medicina Interna del hospital Isidro Ayora Loja-2013 - Romero Mena, Tania Elizabeth (2014)
Organophosphate poisoning is one of the most common in humans, due to the wide availability of these substances on the market in developing countries. Poisoning usually occur accidentally by labor, or intentional exposure to commit suicide. Organophosphorus produce its toxic effects by inhibiting acetylcholinesterase, the enzyme responsible for the hydrolysis of the neurotransmitter acetylcholine, producing acetic acid and choline, chemically inert products. The connection between organophosphates and acetylcholine is spontaneously irreversible binding, however, may be reversible with the use of specific antidotes called oximes. Early administration of pralidoxime is crucial and very useful if started within the first six hours after acute intoxication. Atropine produces a dramatic clinical benefit for muscarinic cholinergic syndrome symptoms. Major complications may occur in patients with organophosphate poisoning, such as hypotension, fatal cardiac arrhythmias, intermediate syndrome, esophagitis, acute renal failure, respiratory distress, pneumonia and even severe cerebral dysfunction. Through this investigation is to determine factors that predispose intake organophosphorus patients treated area Internal Medicine Hospital Isidro Ayora Loja in 2013. The methodology included a structured interview patients who suffered organophosphate poisoning. With the present investigation is concluded that 53.33% (32) has been influenced by the intake of organophosphate social factors, 26.67% (16) by psychological factors and 20.00% (12) by socioeconomic factors. The most frequent sex is the male ingested organophosphates in 53.33% (32) were males. The most common age at which no greater organophosphate poisoning in 40.00% (24) belong to the age range between 10-20 years. The organophosphate that produces acute poisoning most often is a rodenticide (champion) to 33.33% (20), insecticides (malathion) with 25.00%, pesticide (perrofin) to 16.67% (10), antialergeno for dogs and cats (dermofin ) in a 11.67% (7), herbicide (Gramoxone) in a 5.00% (3) and with the same percentage pesticide (furadan) (3) and parasiticidal (Neguvon pellets) with a 3.33% (2). The most common side effects caused by the ingestion of organophosphates are pneumonia at 25%, 18.33% respectively for both esophagitis and prerenalfailure however each 38.34% did not present any adverse effects after treatment organophosphate poisoning. Key words: Organophosphate poisoning social factor, malateon, champion